2011
DOI: 10.24059/olj.v15i1.183
|View full text |Cite
|
Sign up to set email alerts
|

Designed Learner Interactions in Blended Course Delivery

Abstract: In transitioning to a hybrid delivery model, faculty are presented with an opportunity to engage in a systematic instructional design process which can bring coursework in line with pedagogical best practices that may not exist in traditional face-to-face classes. This paper presents a model whereby Marist College Academic Technology & eLearning staff focuses faculty attention on designing effective student interactions with content, the instructor, and other students. These interactions promote deeper lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Brook and Oliver (2003) suggest that the learning technologies need to promote a sense of a community by enabling, supporting and facilitating group communication. Other work provides empirical evidence that the provision of communication tools that enable not only effective communication with the instructor, but also with other students, can significantly influence students' satisfaction and perceived learning (Czerkawski and Lyman, 2016; Eom and Ashill, 2016; Jaggars and Xu, 2016; Lee and Dashew, 2011; Swan, 2001). Consistent with these suggestions and findings, our results show that group communication and participation is a major influencer of satisfaction with group-based new learning methods.…”
Section: Discussionmentioning
confidence: 99%
“…Brook and Oliver (2003) suggest that the learning technologies need to promote a sense of a community by enabling, supporting and facilitating group communication. Other work provides empirical evidence that the provision of communication tools that enable not only effective communication with the instructor, but also with other students, can significantly influence students' satisfaction and perceived learning (Czerkawski and Lyman, 2016; Eom and Ashill, 2016; Jaggars and Xu, 2016; Lee and Dashew, 2011; Swan, 2001). Consistent with these suggestions and findings, our results show that group communication and participation is a major influencer of satisfaction with group-based new learning methods.…”
Section: Discussionmentioning
confidence: 99%
“…Through surveying college faculty members at 14 colleges and universities around the world who taught courses using a blend of face-to-face and online activities, Lee and Dashew (2011) found that instructors rated the ability of their blended-teaching techniques to help students access material as 4.62 on a scale from one (low level of usefulness) to five (high level of usefulness). Effective blended-learning programs are using technology to help students collaborate and increase their depth of understanding in different content areas.…”
Section: Learner-content Interactionsmentioning
confidence: 99%
“…The feedback provided during the learning process should not take charge of the learning process (Flórez& Sammons, 2013). Other than motivating the students, feedback facilitates a comfortable learning environment (Lee & Dashew, 2011). The instructor may encourage the students through questions, challenging their ideas and even formulating the idea to reach the conclusion (Ültanır, 2012).…”
Section: Group Learner Participationmentioning
confidence: 99%